2001
DOI: 10.1177/c10n2r8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crossing Legs on Blood Pressure Measurement

Abstract: The purpose of this study was to determine if blood pressure measurement is affected by the leg crossed at the knee as compared with feet flat on the floor in a well-senior population. Participants (N = 110) either had their blood pressure measured with feet flat first and then crossed or the reverse of this. Results indicate that blood pressure was significantly higher when legs were crossed versus uncrossed. Systolic pressure changed by 5.9 mmHg, from 127.32 to 133.24, whereas diastolic pressure changed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…2005), there was no statistical difference between those with crossed and uncrossed legs in this study. Similar observation has been made in some other studies (Avvampato 2001, Keele‐Smith & Price‐Daniel 2001).…”
Section: Discussionsupporting
confidence: 92%
“…2005), there was no statistical difference between those with crossed and uncrossed legs in this study. Similar observation has been made in some other studies (Avvampato 2001, Keele‐Smith & Price‐Daniel 2001).…”
Section: Discussionsupporting
confidence: 92%
“…There have been only seven publications investigating the effect of crossing leg on BP (Foster‐Fitzpatrick et al 1999, Peters et al 1999, Avvampato 2001, Keele‐Smith and Price‐Daniel 2001, Pinar et al 2004, Adiyaman et al 2007, Van Groningen et al 2008). All of them, except one (Avvampato 2001), showed a BP rise when crossing the legs; however, a broad range of BP rise was present.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, it was concluded that the cardiovascular risk class increased for many patients with hypertension but less for participants with normotension. Keele‐Smith and Price‐Daniel (2001) indicated that BP was significantly higher when legs were crossed vs. uncrossed among 110 participants in a senior population. In a previous study (Pinar et al.…”
Section: Introductionmentioning
confidence: 98%
“…The results of eight studies showed that crossed legs had an impact on measured BP (Foster-Fitzpatrick et al 1999, Peters et al 1999, Avvampato 2001, Keele-Smith and Price-Daniel 2001, Pinar et al 2004, Adiyaman et al 2007, van Groningen et al 2008, van Velthoven et al 2014. In addition to one study (Avvampato 2001), the results of the other seven studies all showed that the readings of SBP and DBP with crossed legs have significantly increased BPs.…”
Section: Crossed Legsmentioning
confidence: 99%